Emerging Digital Technologies: Building Competencies of STEM Pre-Service Teachers - Peter Abayomi Onanuga; Adewale Owodunni Saka (Journal of Teaching and Learning)
This study investigated the level of emerging digital technologies’ competencies of Science, Technology, Engineering, and Mathematics (STEM) pre-service teachers. It employed a descriptive survey research design. A sample of 357 STEM pre-service teachers from a Nigerian university were selected purposively, based on the criteria that they were willing to participate in the online test. The Science, Technology, Engineering and Mathematics Emerging Digital Technologies’ Competencies Test (STEM-EDTCT, r=0.84) was used to collect data online, through a Google form. The data collected were analyzed using descriptive mean, standard deviations, simple percentages, and inferential statistics (independent t-test and analysis of variance). The results showed that the level of emerging digital technologies’ competencies of STEM pre-service teachers was low, regardless of their mode of entry into the university. The study also found a significant gender difference in the level of digital competencies, with male pre-service teachers scoring higher than their female counterparts. Based on the findings, it is recommended that Nigeria’s policy on pre-service teacher-training should focus on acquiring skills and competencies, particularly in digital technologies. STEM pre-service teachers should be equipped with known and emerging technologies to enable them to deliver knowledge and information effectively.